L’Indonésie : Interactions et conflits idéologiques avant la Deuxième Guerre mondiale - Sadria, Modj-ta-ba (Études internationales, 1986)
Since the dawn of the 20th century, three ideologies have been constantly interacting in the Indonesian society, namely Islam, Marxism, and nationalism. Each has played a striking role in the evolution of the movement for independence - which led to independence in 1945. And today each of them wonders to what extent it has been responsible for the coup d'État by General Suharto in 1965. Since in the current situation, the relations which exist between these three trends of thought, in many respects, are reminiscent of those which prevailed during the interwar years, a study of that period may shed new light on an important moment of the history of political thought in Indonesia. The question of relations between Islamic, nationalist, and Marxist thought is a prevalent issue in a country where a population of Muslim creed is held in subordination, and where there exist s an important leftist intellectual movement, with or without a significant working class. Through the history of the anti-Dutch nationalist movements, through the rise of various Islamic movements (Pan-Islamism, the moderen, the "laity") and that of the Islamic parties linked to them (Sarekat Dagang Islam, Sarekat Islam), through the expansion of the social-democratic, socialist and communist parties (ISDU - Indian Social Democratic Union ; PKI - Perserikaten Kommunist de India ; Sarekat Rakjat - People's Association), and finally, through Sukarno's efforts to conciliate all these movements with a view to independence, an attempt is made to show that, in the evolution of the nationalist movement in Indonesia, there are two inherent elements, namely the socialist ideology and Islam. In the light of the case of Indonesia, it is therefore tempting to consider religion and politics as being symbiotic ideologies.